Provisioning for Strengthening the Main Program of Dasawisma Asoka RT 07, Bukit Timah Subdistrict - Dila Erlianti; Pertiwi Sidrat Almuntaha; Yolanda Devina (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
This community service activity aims to improve the understanding and capacity of Dasawisma members in implementing the core Dasawisma programs as an effort to support family health development and community-based empowerment. The activity was conducted at Dasawisma Asoka RT 07, Bukit Timah Sub-district, Dumai Selatan District, Dumai City. The methods used included lectures, simulations, and discussion sessions tailored to the characteristics of adult learners and community practitioners. The results showed an increase in participants' understanding of the roles, functions, and importance of the core Dasawisma programs. Participants demonstrated high enthusiasm and active participation throughout the activity and were able to identify challenges and needs in implementing Dasawisma activities in their neighborhood. This activity contributed positively to strengthening the role of Dasawisma as a frontline community institution in supporting family health programs, environmental cleanliness, and social welfare at the neighborhood level. Continuous assistance is recommended to ensure that the knowledge gained can be consistently implemented and generate sustainable impacts for the community.